A descriptive analysis of poverty among older people in the Philippines - Jose Ramon G. Albert; Arturo Martinez; Aiko Kikkawa; Donghyun Park; Gemma Estrada; Mar Andriel Umali; Joseph Albert Ni\~no Bulan (Asian Development Bank (ADB), 2025)
This study provides a comprehensive analysis of poverty trends among older people in the Philippines, using various data sources. It analyzes both monetary and multidimensional measures of poverty, as well as income sources, expenditure patterns, asset ownership, and living arrangements among older households. The findings reveal complex dynamics and nuanced patterns of poverty among older people, highlighting the limitations of traditional metrics in capturing the full scope of this age group's economic vulnerability. Key findings include the reliance of many older households on remittances, higher spending on essentials like food and health care, and generally lower asset ownership compared to other households. The study also examines the impact of the coronavirus disease pandemic and discusses policy implications for addressing poverty among older people in the Philippines.
Keywords: I32; J11; J14; 330; poverty; older people; Philippines